The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00405-017-4835-x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic supply of facial defects: long-term experience and retrospective analysis on 99 patients

Abstract: The osseointegrated titanium implants with magnet support provide a reliable attachment for prosthesis and constitute a promising alternative to surgical reconstruction of complex facial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
0
20
0
5
Order By: Relevance
“…Total removal of the orbital contents was first described as orbital exenteration by Georg Barish in 1583 [ 3 , 4 ] and is now a common surgical procedure that has several categories depending upon the patient’s malignancy status and the degree of partial excision of the eyelids [ 5 ]. Orbital and oculofacial prostheses have been considered the most ideal and viable alternative reconstruction method compared with local flap repositioning or microvascular free-flap coverage [ 6 ]. Retention of orbital prosthesis has been achieved using adhesives, attachment to eyeglasses frames or straps, and, more recently, use of dental implants [ 1 , 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total removal of the orbital contents was first described as orbital exenteration by Georg Barish in 1583 [ 3 , 4 ] and is now a common surgical procedure that has several categories depending upon the patient’s malignancy status and the degree of partial excision of the eyelids [ 5 ]. Orbital and oculofacial prostheses have been considered the most ideal and viable alternative reconstruction method compared with local flap repositioning or microvascular free-flap coverage [ 6 ]. Retention of orbital prosthesis has been achieved using adhesives, attachment to eyeglasses frames or straps, and, more recently, use of dental implants [ 1 , 2 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[305] Furthermore, many traditional methods and materials are supported by long-term retrospective studies demonstrating robustness and biocompatibility giving practitioners confidence in their efficacy. [2,65,306,307] Aside from the fabrication process itself, other vital components of the advanced manufacturing pipeline require substantial development, such as 3D scanning and computer modeling. For example, high-accuracy scanners still remain expensive and challenging to use.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…A retrospective study by Karakoca et al (2010) evaluated 25 orbital and 13 nasal prostheses and found an estimated mean survival time of 14.5 months for the first of the patient's prosthesis, with common complications involving clip activation, bar screw and abutment loosening and detaching of the silicone from the acrylic substructure (Karakoca et al, 2010). A larger retrospective study involving 99 patients with custom facial prostheses was carried out by Papaspyrou et al in 2018(Papaspyrou et al, 2018. This included 53 patients with ear prostheses, 27 with eye prostheses and 19 with nasal prostheses with 82.8% or the prostheses designed to be magnetically attached via osseointegrated implants.…”
Section: Patient Wellbeingmentioning
confidence: 99%